Building welcoming and inclusive congregations: Biblical hospitality as a theological paradigm - Shirley, Timothy W. (Verbum et ecclesia, 2024)
This article addresses the question, ‘how can congregations that exhibit prejudice toward LGBTQQIA+ persons (different expressions of nonheterosexuality), overcome bias and discriminatory practices to become missionally holistic, hospitably welcoming, and inclusive of these individuals?’. The answer can be found in engaging an alternative biblical hermeneutic that emphasises the socio-historical context of a given narrative, thus creating a broader and deeper understanding of the principle of biblical hospitality as a fundamental theological premise inherent within the Judeo-Christian scriptures. Accomplishing transformative change demands intentionality by clergy equipped to engage the issues effectively. Pastoral ministers must cultivate the exegetical skills needed to guide local missional churches towards greater inclusivity, with the goal of creating more hospitably welcoming and inclusive faith communities. Intradisciplinary and/or interdisciplinary implications: This article engages a dialogue between biblical and practical theology as missional praxis supporting congregational development as ecclesial reformational transformation to enable local churches to become hospitably welcoming and inclusive.